2014
DOI: 10.1097/pgp.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Current Morphologic Criteria Perform Poorly in Identifying Hereditary Leiomyomatosis and Renal Cell Carcinoma Syndrome-associated Uterine Leiomyomas

Abstract: The contemporary oncologic pathology report conveys diagnostic, prognostic, predictive, and hereditary predisposition information. Each component may be premised on a morphologic feature or a biomarker. Clinical validity and reproducibility are paramount as is standardization of reporting and clinical response to ensure individualization of patient care. Regarding hereditary predisposition, morphology-based genetic referral systems in some instances have eclipsed genealogy-based systems, for example, cell type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…FH deficiency has been shown to be overrepresented in leiomyomas with bizarre nuclei and some of the morphologic features typical for these tumors have been associated with FH mutations [42, 44–47]. Even though morphologic features alone lack robustness to separate sporadic and HLRCC-associated ULs [4850], the possibility of an underlying germline FH mutation should be considered in patients with ULs with bizarre nuclei. Clinical features such as the severity of symptoms, number of tumors within the uterus, age at diagnosis, and possible family history of ULs can be evaluated, and patients should be examined for possible cutaneous leiomyomas.…”
Section: Resultsmentioning
confidence: 99%
“…FH deficiency has been shown to be overrepresented in leiomyomas with bizarre nuclei and some of the morphologic features typical for these tumors have been associated with FH mutations [42, 44–47]. Even though morphologic features alone lack robustness to separate sporadic and HLRCC-associated ULs [4850], the possibility of an underlying germline FH mutation should be considered in patients with ULs with bizarre nuclei. Clinical features such as the severity of symptoms, number of tumors within the uterus, age at diagnosis, and possible family history of ULs can be evaluated, and patients should be examined for possible cutaneous leiomyomas.…”
Section: Resultsmentioning
confidence: 99%
“…[48][49][50] However, these features are not easily reproducible and it has been shown that leiomyomas with bizarre nuclei that are not associated with this syndrome can also show absence of staining for FH (Figure 4d) with positive S2C in the same cells, indicating that the above morphologic features are not diagnostic of this syndrome. 48,51 Thus, absence of staining should be used as a "triage" for further genetic testing but not as a diagnostic tool in this scenario. Finally, avoid using the term atypical leiomyoma for a leiomyoma with bizarre nuclei/symplastic leiomyoma as this term is used in the most recent WHO classification as a synonym of smooth muscle tumor of uncertain/low malignant potential.…”
Section: Tumor Cell Necrosismentioning
confidence: 99%
“…It has previously been suggested that uterine leiomyomas arising in the setting of germline FH mutation may show distinctive morphologic features including prominent nucleoli with perinucleolar clearing, hypercellularity, symplastic-type nuclear atypia, a hemangiopericytomatous vascular pattern, cytoplasmic globules, and stromal edema. 7 , 10 , 11 However, the significance and specificity of these features has recently been questioned, 8 and it seems that morphology alone will be inadequate to identify HLRCC-associated uterine leiomyomas prospectively. 10 …”
mentioning
confidence: 99%
“… 7 , 10 , 11 However, the significance and specificity of these features has recently been questioned, 8 and it seems that morphology alone will be inadequate to identify HLRCC-associated uterine leiomyomas prospectively. 10 …”
mentioning
confidence: 99%
See 1 more Smart Citation